ANALYSIS OF STUDENT ACADEMIC ACHIEVEMENT LEVELS USING FUZZY LOGIC - Nofri Yoliadi, Dodi (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
The purpose of this study is to use fuzzy logic to analyze and retrieve data about student performance levels. This data will later be used to facilitate the analysis of the performance of SMP Negeri 5 Batusangkar students. Data for this study were obtained through observation and literature review from a variety of sources. The results of this survey analysis make it easier for teachers to analyze student performance without manual searches, and the ability to quickly process values ​​using the provided media such as Microsoft Excel, Access, etc. We provide accurate and accurate data. When judging the characteristics of a student's level of academic performance, she complies with the Order of the Minister of Education, Culture, Research and Technology (Permendikbudristok) No. 21 of 2022 on Educational Evaluation Standards. Analyzing student performance levels is performed using a fuzzy logic database by mapping student results based on variables. Ethics of use, knowledge and aspects of information (attitudes). This technique is tested using Microsoft Excel to query the designed data.